A new Stygarctus (Arthrotardigrada: Stygarctidae) from Japan, with entangled seminal receptacle ducts - Fujimoto, Shinta (Zootaxa, 2014)
Stygarctus ayatori sp. nov. (Arthrotardigrada: Stygarctidae), is described from a sandy beach located at Okinoshima, Tateyama Bay, Boso Peninsula, Honshu, Japan. The most prominent characters were observed in the female genital structure, with the seminal receptacle ducts forming a three-dimensional entanglement near the exterior opening, and internal thickening situated peripheral to the gonopore and between the gonopore and anus. The new species is distinguished from the congeners by these characters; excluding S. abornatus McKirdy et al., 1976 for which there is no information on the genital structure. However, S. ayatori sp. nov. and S. abornatus can be differentiated by the presence of dorsal spines on the former species, which are absent from the latter.